La lógica del lenguaje y sus estrategias para otorgar identidades - Helberg Chávez, Heinrich (2021)
This work deals with the logical and philosophical problems of everyday language logic. We do this within the framework of a vision of language as a social practice that sustains itself. The identity of things is not objective as a secluded essence that gives identity despite the diverse appearance, but as a social practice that confers identity according to the judgments and reasons that speakers argue when they speak, based on their daily knowledge and way of life, which serve as a framework of immediate reference. This approach also allows to shed a different light on classical philosophical problems such as those posed by The Philosophy of Heráclito.